DESKRIPSI MISKONSEPSI SISWA TENTANG KONSEP-KONSEP DALAM RANGKAIAN LISTRIK - Hamdani, Hamdani (Universitas Tanjungpura, 2013)
The aim of this research were investigated misconception about electric circuit. Diagnostic tests and Certainly of Response Index used to survey 68 students in Pontianak. That misconceptions are current have been consumed by its closed circuit components; the more battery in the circuits, the more brightness of the bulb; the more of resistance in series circuits, the more current; battery to be seen as stationary source of current; if a circuit element changed in a circuit, student analyse circuit in terms before and after current passes that place; if the number of resistance increase in a circuit, equivalent resistance also increases as independent from their connection type.Â Keywords: misconception, electric circuit, CRI, diagnostic tests.